Prevalence and determinants of HIV testing among men in India: Insights from NFHS-5 - Ajay Dutta; Ajay Murmu (Clinical Epidemiology and Global Health)
Background: India, despite its traditional societal values, faces a significant public health challenge with its high prevalence of HIV/AIDS, ranking third globally in the number of people living with HIV. Therefore, HIV testing serves as a critical entry point for HIV prevention, treatment and care, yet testing rates among men remain low. The study aims to explore the prevalence of HIV testing among men aged 15–54 in India and identify the key determinants influencing testing behaviour. Data & method: Data were drawn from the fifth round of the National Family Health Survey (NFHS-5), 2019–21. The analysis was carried out with 58,465 samples. The outcome variable was ever tested for HIV among men aged 15–54. Independent variables include a wide range of socio-economic, demographic, and behavioural factors. Bivariate analysis and binary logistic regression were used to analyze the data. Result: The study estimated that 12.6 % of men aged 29 and above, 12.4 % of married men, 15.9 % of men who had higher education, 17.6 % of men who had paid for sex, and 25 % of men engaging in high-risk sexual behaviour have been tested for HIV. Results from the binary logistic regression indicate that several factors were significantly associated with HIV testing, including age, marital status, religion, place of residence, educational level, wealth quintile, occupation, alcohol consumption, media exposure, paid for sex in the last 12 months, sexual intercourse with others, genital discharge, risky sexual behaviour, and health insurance coverage were significantly associated with HIV testing. Conclusion: The findings suggest a tailored approach to formulate effective policies considering HIV testing among men and increasing awareness of the negative implications of not getting an HIV test.